Long chain n-3 polyunsaturated fatty acids are not associated with circulating T-helper type 1 cells: Results from the Multi-Ethnic Study of Atherosclerosis (MESA). (October 2017) - Sagawa, Naoko; Olson, Nels C.; Ahuja, Vasudha; Vishnu, Abhishek; Doyle, Margaret F.; Psaty, Bruce M.; Jenny, Nancy Swords; Siscovick, David S.; Lemaitre, Rozenn N.; Steffen, Lyn M.; Tsai, Michael Y.; Sekikawa, Akira
Abstract: T-helper type 1 (Th1) cells are pro-inflammatory and provide signals to immune cells. Animal models and in vitro human cell culture experiments have indicated that long chain n-3 polyunsaturated fatty acids (LCn3PUFAs) reduce Th1 cell levels; however, the association is unknown in healthy humans. We hypothesized that circulating levels and dietary intake of LCn3PUFAs have an inverse association with circulating levels of Th1 cells and studied 895 participants in the Multi-Ethnic Study of Atherosclerosis (age 61 ± 10 years at exam 1, 52% women, 44% white, 21% African-American, 24% Hispanic-American, 11% Chinese-American). Phospholipid LCn3PUFAs (% of total fatty acids), measured by gas chromatography, and intake of LCn3PUFAs, evaluated by food frequency questionnaire, were evaluated at exam 1 (2000-02) and defined as the sum of eicosapentaenoic and docosahexaenoic acids. Th1 cells were measured by flow cytometry at exam 4 (2005-07), expressed as a percentage of CD4 + lymphocytes that were interferon-γ + (%Th1: CD4 + IFN-γ + ). Median (interquartile range) plasma LCn3PUFA, dietary LCn3PUFA, and %Th1 levels were 4.31% (3.40–5.82%), 0.09 (0.05–0.16) g/day, and 14.4% (9.8–20.0%), respectively. When the association of LCn3PUFA-quartiles with %Th1 was analyzed using general linear models, neither plasma nor dietary LCn3PUFAs were significantly associated with %Th1 ( P -trend = 0.58 and 0.80, respectively), which remained even after adjusting for demographics, lifestyle factors, lipids, season, and cytomegalovirus titers. In this multi-ethnic U.S. population, circulating levels and dietary intake of LCn3PUFAs were not significantly associated with Th1 cell levels. Further research is needed to assess potential benefits of supplementation and much higher dietary consumption of LCn3PUFAs on Th1 cells. Highlights: LCn3PUFAs are associated with lower Th1 cell levels in animal and in vitro studies. The association of LCn3PUFAs and Th1 cell levels is unknown in healthy humans. LCn3PUFas were not asociated with Th1 cell levels in our multi-ethnic U.S. cohort. Null results were with both plasma and dietary intakes of LCn3PUFAs. LCn3PUFA levels in our cohort may have been too low for immunomodulatory effects.